CHONDROREGENERATIVE POTENTIAL ON SUBCUTANEOUS IMPLANTATION OF PLATELET-RICH FIBRIN (PRF)-IMPREGNATED DECELLULARIZED BOVINE CARTILAGE SCAFFOLD - Widyatmika, Putu Ardhy Parama; Noer, M. Sjaifuddin; Hutagalung, Magda Rosalina (Journal of Stem Cell Research and Tissue Engineering, 2023)
The discovery of alternative implants with regenerative potential comparable to autologous cartilage continues to be encouraged because of the high donor site morbidity rate. This research tries to make an alternative implant that uses the concept of tissue engineering techniques in the form of endogenous regeneration by combining Decellularized Bovine Cartilage scaffold with Platelet-Rich Fibrin (BCPRF) which is implanted subcutaneously. The aim of this study was to compare the potential for chondroregeneration between BCPRF and autologous cartilage as assessed by chondrocyte cell formation, type 2 collagen thickness, and implant resorption rate in subcutaneous implantation. Using the research design method is a pretest-posttest control group design using New Zealand white rabbits. Forty eight experimental samples were divided into 2 groups which were treated with BCPRF and autologous cartilage implantation. Results were evaluated after 6 weeks. Evaluation was carried out on 39 samples. Microscopy showed better potential for autologous cartilage chondroregeneration than BCPRF with significant differences in the number of chondrocytes formed, the thickness of type 2 collagen (p=0.000), and the rate of implant resorption (p=0.000). In conclusion, the potential for chondroregeneration of autologous cartilage and BCPRF is significantly different in terms of the number of chondrocytes formed, the thickness of type 2 collagen, and the rate of implant resorption.